2022-LBA-750-ESGO Rectal cancer versus endometriosis on ultrasound in metastatic ovary. (27th October 2022) - Elagwany, Ahmed
Abstract : Introduction: Ultrasound is now available everywhere with high advancement in technology. There are some findings on ultrasound that can be very similar on appearance. These include the rectal endometriosis and rectal cancer especially if there is adnexal masses associated. Methods we are aiming here to show the difference and illustrate the findings for differentiation through presentation of 2 different cases. Results: IOTA scoring system is very important in initial assessment of masses, and it can be memorized easily. And after its application, expert ultrasound can help with pattern recognition of masses. Rectal cancer and rectal endometriosis can be easily mistaken or even can be missed so we aimed here to clarify them through discussion od 2 cases. Furthermore, mucin cancer typical appearance was not reported before on literature regarding the typical intestinal mucinous cystadenocrcinoma of the ovary and metastatic ovary with vessels sign also are shown here in a typical appearance. Conclusions finally we aimed to show some ultrasound findings that was previously can be seen on ultrasound, now with advancement in technology, we can so that even better than the MRI and CT especially in the pelvic region.